(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Legal responsibility of medical workers for committing an offense is the application of measures of state coercion to the person who committed the offense. In practical terms, legal responsibility arises when a legal conflict in the field of medical care has arisen and all the means of resolving it have already been exhausted. Essentially, the responsibility of a doctor means the measure of the state’s influence on a person who, for one reason or another, has committed an act contrary to the norms and rules adopted in medicine. It is important to note that first of all it is a violation of the professional duties of the doctor.